Critical Literacy Strategy and Challenges: Voice from a High School EFL Teacher - Hidayat, Raden Aulia Utami; Gustine, Gin Gin; Setyarini, Sri (Universitas Pendidikan Indonesia, 2020)
This qualitative case study is proposed to investigate the implementation of critical literacy strategy in the English as a Foreign Language (EFL) classroom by one English teacher from one of the public senior high school in Indonesia. The qualitative analysis of the data collected from classroom observation and interview show that the teacher implements the five-steps instructional framework of critical literacy. In the implementation stage, the teacher conducted the framework's whole steps and emphasized the group discussion session where the students could be free to state their opinion. Although the material was taken from the textbook, the teacher could combine her teaching between the book and critical literacy teaching. She provoked her students by posing essential questions and helped students to read and think beyond the text. She also tried to develop her students' social awareness, tolerance, and responsibility through the discussion they shared. However, the teacher encountered some challenges in implementing critical literacy, such as the lack of students' language proficiency, classroom practice transformation, and the lack of teaching resources and facilities.